A methodology for optimum delay, skew, and power performances in an FPGA clock network - Sulaiman, Mohd S. (2006)
A methodology for FPGA clock network optimisation is presented. The algorithms for optimisation of clock skew, delay, and power considering slew rate constraint for an FPGA fixed-clock network are implemented and verified on SX 32 FPGA chip. Measurements indicated a 60% reduction in clock slew rate and a 22% improvement in power dissipation when compared to the results of the initial, un-optimised chip.